Abolishment of high-risk left lateral accessory pathway by myocardial infarction: a blessing in disguise? A case report. Issue 2 (16th February 2021) - O'Brien, Jim; Kozhuharov, Nikola; Chin, Shui Hao; Hall, Mark
Abstract: Background: Antegradely conducting left lateral accessory pathways are a risk for supraventricular tachycardias and pre-excited atrial fibrillation. Rarely, an anomalous coronary sinus can cause difficulty in locating the pathway. The left circumflex coronary artery and obtuse marginal branches supply the posterolateral left ventricle. We describe a case report of a high-risk accessory pathway associated with an anomalous coronary sinus which, between successive electrophysiology studies, was obliterated by a felicitous acute coronary syndrome in the left circumflex territory. Case summary: A 49-year-old male with palpitations and manifest pre-excitation was referred for electrophysiology study. Initial study revealed a high-risk left lateral accessory pathway with antegrade effective refractory period of 240 ms and rapidly conducting pre-excited atrial fibrillation. The coronary sinus could not be cannulated to localize the pathway. Coronary angiography and cardiac computed tomography showed an anomalous coronary sinus emptying into the right atrial free wall and patent coronaries. While awaiting repeat electrophysiology study, the patient suffered an acute coronary syndrome with immediate loss of previously visible pre-excitation on electrocardiogram, and underwent stenting of an occluded marginal branch of the circumflex. Repeat electrophysiology study demonstrated a now low-risk accessory pathway (effective refractory period 390 ms). Since infarction, the patient's palpitations have fully settled with all subsequent electrocardiograms devoid of manifest pre-excitation. Discussion: Left lateral accessory pathways, which can associate with an anomalous coronary sinus, derive from tissue similar to normal ventricular myocardium and are vulnerable to ischaemic insults in the area subtended by the circumflex artery.